Мотиваційний аспект формування у майбутніх педагогів закладів вищої освіти цифрової компетентності - Мирошниченко, Олена Анатоліївна; Myroshnychenko, O. (My University, 2019)
Статтю присвячено пошуку шляхів формування позитивних мотивів у майбутніх педагогів закладів вищої освіти до застосування ІКТ у професійній діяльності з позицій теорії та методики професійної освіти. Наголошено, що швидкими темпами відбувається оновлення технічної бази ІКТ. Це вимагає належного осмислення цих процесів та оперативного реагування у вигляді розробки психолого-педагогічних і методичних основ застосування цифрових технологій у навчальному процесі. Показано, що проблема формування у майбутніх педагогів закладів вищої освіти позитивних мотивів до застосування ІКТ у професійній діяльності, комплексного володіння цифровими технологіями є вельми актуальною в теорії та методиці професійної освіти. Запропоновано шляхи формування позитивної мотивації у майбутніх педагогів закладів вищої освіти в аспекті розвитку у них цифрової компетентності: необхідно сформувати у майбутніх педагогів закладів вищої освіти чітке розуміння того, що без оволодіння на високому рівні цифровою компетентністю неможливі професійний розвиток і професійне самовдосконалення. The article is dedicated to searching the ways how to form positive motives among prospective educators in higher education establishments as for applying DC in professional activity from the stance of professional theory and methodology. It’s emphasized that the technological base of ICT is being updated rapidly. This requires proper understanding of these processes and prompt response in the form of developing psychological, pedagogical and methodological bases for the use of digital technologies in the educational process. It is shown that the problem of formation of future teachers of higher education institutions with positive motives for the use of ICT in professional activity, integrated digital skills is very relevant in the theory and methodology of vocational education.The following ways to form a positive motivation among prospective educators of higher education establishments are suggested from the position of digital competence development: to form among prospective educators of higher education establishments a clear understanding of the fact that without high level knowledge of digital competence their professional development and self-perfection are impossible. Such understanding ensures formation of a positive motivation among Master’s students concerning adopting knowledge, skills, methods of activity and aptitudes that refer directly to DC and applying digital technology in educating process in particular and in professional activity in general; strengthening of professional selfesteem of a perspective educatorof higher education establishment, formation of confidence that he/she will be able to adopt DC and digital tools of teaching successfully from the position of using them in an education process; creation of information and education environment, immersion in which will encourage a student’s formation of an appropriate motivation to receive digital competence; context education, especially in the form of quasiprofessional teaching: modeling of pedagogical teacher’s activity applying digital methods of teaching, students’ mutual control of their knowledge applying DC, carrying out other social and role functions of a teacher by Master’s students.
Motivational aspect of digital competence formation among higher establishment educators
Keywords: потреба; мотивація; цифрова компетентність; інформаційно-комунікаційні технології; інформаційно-освітнє середовище; necessity; motivation; digital competency; information and communication technology; information and education environment